Chronic exposure to heavy metals and risk of oral cancer in Taiwanese males - Su, Che-Chun; Tsai, Kuo-Yang; Hsu, Yun-Ying; Lin, Yo-Yu; Lian, Ie-Bin (Oral oncology, 2010)
The incidence of oral cancer has increased rapidly over the past 20 years in Taiwan. Cigarette smoking and betel quid chewing are considered as the most important risk factors. However, we found that Changhua, a county in Taiwan, had the highest oral cancer incidence, but a modest prevalence of smoking and betel quid chewing. Our previous study found that the incidence of oral cancer in Taiwan has a strong spatial correlation with the heavy metal concentrations in farm soils of patients’ residential areas. A high content of heavy metals in farm soil is likely the result of industrial activities. If exposure to heavy metals is a risk factor for oral cancer, we would expect to find evidence from epidemiologic trends. The age–period–cohort model was used to analyze chart records from the Taiwan Cancer Registry of 21,135 male patients diagnosed with oral cancer from 1983 to 2002. Although the incidence increased in both Changhua and Taiwan overall, Changhua had a similar incidence to that in Taiwan as a whole until 1990, when the incidence in Changhua began to speed up, leaving a marked difference with that in Taiwan. Exposure to the heavy metal pollution for a period of more than 10 years has an impact on the incidence of oral cancer. This novel factor can explain the extremely high incidence in Changhua.